PENGARUH MOTIVASI, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. KENCANA SAWIT INDONESIA - Doni Marlius; Ilin Pebrina (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine the effect of motivation, compensation and discipline of monkeys on employee performance at PT. Kencana Sawit Indonesia, this research is a quantitative research, the sampling method uses a total sampling with the number of respondents 50 people. The data analysis technique used in this study was multiple linear regression analysis. The results of this study indicate that motivation has a positive and significant effect on employee performance, compensation has no effect on employee performance, and ape discipline has a positive and significant effect on employee performance